Non-phisical Tourism Infrastructure; How Specific Allocation Fund (DAK) Contributes to Local Human Resources? - Muh Hilmi Pauzi; Musleh; Evilia Rochmi; Mahrun; Riadatus Solihin (JMET: Journal of Management Entrepreneurship and Tourism, 2023)
This research aims to elaborate the use of special allocation funds to welcome the acceleration of tourism development through empowerment activities and tourism skills training in Central Lombok district. This research adopts a qualitative approach with a case study type. Data collected from primary and secondary sources such as the tourism office as the organizer and training participants as program beneficiaries are processed descriptively based on the participants' narratives. Documents in the form of photos and activity reports also become skunder data to be processed to support primary data. The results showed that the Special Allocation Fund (DAK) allocated by the central order for the development of the tourism industry in Central Lombok district to develop non-physical infrastructure was used for the needs of increasing human resources through various programs that have been successfully implemented. The government collaborates with communities who have high motivation for the development of pariwisaata in Central Lombok. Programs that have been successfully implemented; digitalization, security and safety in tourist destinations, training of tour guides (artificial, cultural and natural), training on tourism village management and training on improving innovation and hygiene of culinary dishes. The empowerment program was initiated to increase the capacity and capability of trained and certified tourism personnel. The acceleration of increasing the capacity of tourism resources in the future can be spread evenly to tourism villages and the time is longer so that the effectiveness of training can be absorbed properly.